Editorial: A Historical Critique of Globalization Optimism - Mahayasa, Dias Pabyantara Swandita; Utami, Arum Tri (JUSS (Jurnal Sosial Soedirman), 2025)
Editorial: A Historical Critique of Globalization Optimism